Differences in nutritional and psychological habits in hypertension patients (2022)
Multifactorial factors such as psychological and nutritional habits are controlling factors in hypertension. The aim of the present study was to analyze differences in nutritional and psychological habits in humans with hypertension. Fifty participants with hypertension (HG) (57.5 ± 13.6 years) and 100 participants as control group (CG) with no hypertension disease (48.9 ± 7.9 years) were interviewed via online questionnaire. Multifactorial items in nutrition habits and psychological profile were analyzed by a compendium of questionnaires; psychological measures refer to personality, anxiety, depression, loneliness, perceived stress, and psychological inflexibility; and a nutritional questionnaire to analyze eating habits and nutrition behaviors of the participants. CG showed significantly higher week vitality (p = 0.001), juice weekly consumption (p = 0.011), coffee weekly consumption (p = 0.050), fermented milk weekly consumption (p = 0.004), and fruit weekly consumption (p = 0.022) than HG. Lower values of weekly coffee consumption and week vitality were found in HG. According to the psychological profile, significant differences were found only depression values, finding HG more depressed than CG (p = 0.002). In conclusion, our results showed that people with better nutrition and mental health would present lower levels of blood pressure. Therefore, the combination of psychological therapy and nutritional recommendations for reducing the risk of having hypertension and improving the blood pressure levels may be needed for patient with hypertension.